Early (years) reactions: comparative analysis of early childhood policies and programs during the first wave of the COVID-19 pandemic - Joanne Kearon; Sarah Carsley; Meta van den Heuvel; Jessica Hopkins (BMC, 2022)
Abstract Background During the first wave of COVID-19 there was little evidence to guide appropriate child and family programs and policy supports. Methods We compared policies and programs implemented to support early child health and well-being during the first wave of COVID-19 in Australia, Canada, the Netherlands, Singapore, the UK, and the USA. Program and policy themes were focused on prenatal care, well-baby visits and immunization schedules, financial supports, domestic violence and housing, childcare supports, child protective services, and food security. Results Significant heterogeneity in implementation of OECD-recommended policy responses was found with all of the included countries implementing some of these policies, but no country implementing supports in all of the potential areas. Conclusions This analysis gives insight into initial government reactions to support children and families, and opportunities for governments to implement further supportive programs and policies during the current pandemic and future emergencies.